Pemberdayaan dan Pelatihan Pembuatan Tampon dan Perlengkapan Kedokteran Gigi pada Ibu Rumah Tangga di Kelurahan Makasar, Kecamatan Makasar, Jakarta Timur - Rosalina Tjandrawinata; Dody Prayitno; Deviyanti Pratiwi; Florencia Livia Kurniawan; Sastra Kusuma Widjaya; Thomas Aurelius Dharma; Yoana Winardi; Tiffany Hartono (JURNAL ABDIMAS KESEHATAN TERPADU, 2023)
Makasar is a sub-district in East Jakarta Municipality, DKI Jakarta Raya Province. Previously, it was called Kampung Makassar. The women's group in Makasar sub-district already has skills in making dental tampons, perforated cloth mat named ‘duk bolong’, and medical head caps. However, their business/sales distribution knowledge needs to be developed so that their creations can be sold widely and then the result can improve the economy of Makasar sub-district resident. Dental tampon makers in the Makasar sub-district also need counseling regarding the importance of cleanliness in the manufacturing area and supporting equipment for sterilizing the tampons’duk bolong’, and medical head caps so that the products have higher value and ready to use for both public and private use. Besides, the training provided counseling and demonstration on how to create interesting promotion through online media. The results of the counseling are very good and there is an increase in the skills and knowledge of the women in the Makassar sub-district in product manufacture and product marketing.